Early pregnancies among middle school students: Attribution of blame and the feelings of responsibility among teachers and parents - Fute, Antony; Sun, Binghai; Oubibi, Mohamed (Frontiers in Psychology, 2022)
Globally, 15% of adolescents give birth before turning 18. This study used an online survey with 201 teachers and 317 parents to explore and compare their empathetic concern, feelings of responsibility, and attribution of blame for pregnancy among school girls. SPSS 26 generated results indicated a significant mean difference between parents and teachers on empathy (t =5.735, p<.001), attribution of blame (t=6.902, p< 0.001), and feelings of responsibility (t=1.727, p<.001). Except for attribution of blame, parents' mean scores of other variables were higher than that of teachers. Understanding social feelings about their responsibilities are essential for fighting against early pregnancy